Pattern of Water Use and Seed Yield under Terminal Drought in Chickpea Genotypes - Pang, Jiayin; Turner, Neil C.; Du, Yan-Lei; Colmer, Timothy D.; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2017)
Drought, particularly terminal drought, reduces the yield of chickpea (Cicer arietinum L.). Terminal drought tolerance and water use patterns were evaluated under controlled conditions in 10 genotypes of desi chickpea. Withholding water from early podding reduced vegetative growth, reproductive growth, seed yield and water use efficiency for seed yield in all genotypes. The genotype Neelam, which produced the highest seed yield when water was withheld, used the least water when well-watered; however, its aboveground biomass at maturity did not differ significantly from six of the nine other genotypes. Indeed, the water-stressed Neelam had the lowest daily transpiration rate during the early stages of water stress and the highest during the later stages, thereby maintaining the highest soil water content in the first 16 days after water was withheld, which enabled higher pod production, lower pod abortion and better seed filling. Genotypes differed in threshold value of fraction of transpirable soil water when flowering and seed set ceased in the water-stress treatment. We conclude that a conservative water use strategy benefits seed yield of chickpea exposed to water shortage during early podding.